The ways of the causes and its practices on Taiser Atfseer for The Scholar Sheikh Amuhammad bin Yousf Atfish - AL- BATTASHI, HILAL BIN KHALFAN BIN MOHAMMED (Journal of Islamic Sciences, 2019)
This study sheds light on the approach of the Scholar Muhammad ibn Yusuf AL Atfish in the ways and methods of his interpretation of The Holy Quran (Taiser Atfseer) .This study was depending on scientific approach which is represented on inductive approach with deductive approach. The study concluded that Scholar Atfish has his own opinions and practices which are connected with ways of the causality which is circled on it ( AL qyas operation) , even that he denied that some phrases and skills refers to the casuality, The study recommended that researchers in the fundamentals of jurisprudence need to research on the jurisprudence of Ibadhism and distinguish the fundamental matters of it and collecting its scattering and study it deeply and explaining the ways of the fundamental scholars who do not have any independent fundamental books.
Keywords: text; casuality; derived; explicit; apparent; rout; cause